Sex differences in symptom presentation and functional outcomes: a pilot study in a matched sample of veterans with mild TBI. (20th March 2020) - Gray, Max; Adamson, Maheen M.; Thompson, Ryan C.; Kapphahn, Kristopher I.; Han, Summer; Chung, Joyce S.; Harris, Odette A.
ABSTRACT: Primary Objective : Research focused on mild traumatic brain injury in active military and veteran populations details the psychological, neurological and functional outcomes of mTBI, in a primarily male (~95%) cohort. This may misrepresent female symptoms and outcomes. Here we assess for genuine sex differences in symptom presentation and functional outcomes. Research Design : We used matched pairs to preclude potential sex bias in outcome data. Methods and Procedures : We matched 49 female/male pairs on; 1) mechanism of injury, 2) time from injury to assessment and 3) age at assessment. Statistics were t-tests, chi-square, correlations and post hoc linear regression. Main outcomes and results : Outcome assessment revealed four significant ( p < .05) sex differences; Living situation, Marital status, Vocation and Branch of service. Only the Neurobehavioral Symptom Inventory (NSI) composite cognitive domain factor was significantly different between females (mean: 10.26) and males (mean: 7.58). Linear regression confirmed a significant effect of sex for the cognitive composite ( p = .002). Conclusion : We conclude that sex has a moderate effect on mTBI post-concussive symptom presentation. The significant sex difference in the NSI cognitive domain characterizes sex-related symptomology profiles providers can focus on for better rehabilitation management. Replication in the larger cohort would improve generalizability. Abbreviation: TBI: Traumatic Brain Injuries; mTBI: mild Traumatic Brain Injuries; OIF: Operation Iraqi Freedom; OEF: Operation Enduring Freedom; VA: Veterans Affairs Health Care System; PSC: Polytrauma System of Care; PRC: Polytrauma Rehabilitation Center; PTRP: Polytrauma Transitional Rehabilitation Program; PNS: Polytrauma Network Site; PTSD: Post Traumatic Stress Disorder; DoD: Department of Defense; NSI: Neurobehavioral Symptom Inventory; LOC: loss of consciousness; AOC: alteration of consciousness; PTA: posttraumatic amnesia; CPRS: computerized patient record system; CTBIE: Comprehensive TBI Evaluation; OCD: obsessive compulsive disorder; ETOH: alcohol abuse